Cross-cultural adaptation and content validity of an instrument to determine palliative needs in Colombia - Celis Moreno, Jhonatan Sebastian; Vargas Pelaez, Maribel (Horizonte Sanitario, 2022)
Objetive: Carry out the cross-cultural adaptation and to evaluate thevalidity of the content into Spanish of the NECPAL instrument ofCCOMS© for patients admitted to the ICU for use in Colombia.Materials and methods: Methodological study of cross-culturaladaptation and content validity. Data collection was carried out fromJune to November 2020. The sample consisted of 12 specialists. TheNECPAL instrument was evaluated determining the transcendence andthe items, identifying the clarity, pertinence and relevance. To evaluateeach item, a 3-level Likert-type scale was used. Content validity wasassessed using Lawshe's Content Validity Index (CVI)Results: It was determined that the NECPAL instrument is suitable foruse in the Colombian context. Adjustments were made to improve yourperformance. The IVC of the NECPAL instrument was 0.96.Conclusions: The NECPAL instrument in its Colombian Spanishversion is appropriate to determine palliative needs in patientshospitalized in the ICU.Key words: Palliative care; Needs assessment; Critical Care; Chronic disease; Validation Study